Posicionamento estratégico das cadeias multinacionais de hotéis na avaliação de mercado hoteleiro brasileiro para negócios - Coriolano, Plínio Vidigal (1998)
The main objective of this study is to utilize an exploratory/explanatory research methodology to analyze the strategic positioning of multinational hotel chains in the evaluation of the Brazilian hotel market attractiveness for business. An analytic framework is developed based primarily on the literature review of multinational strategy, international business theories and concepts, and hospitality management strategy so as to enable the discussion of the research problem: <to what extent the strategic positioning for business of multinational hotel chains reflects the CEOs' attractiveness perception of the Brazilian hotel market>. A qualitative research approach was used. According to the criteria selected, 20 multinational hotel chains formed the research universe, out of which 14 agreed on participating. The data were coliected through responses to a questionnaire sent to leading lodging multinationals, analyzed through summary tables and graphs. Nearly ali respondents perceive the market as having growth potential, therefore with striking interest. The findings from the research lead to the assumption that two distinctive groups of hotel chains have different strategic positionings toward the Brazilian market. If for the hotel chains present in the market this positioning - evaluated through research questions - matches with the CEOs' attractiveness perception of the market, for hotels absent from the market this match is not always clear, specially due to the lack of consistent information gathering and a certain disregard of competition movements. Supporting the conclusions, six propositions were included and validated in order to criss-cross the research questions and - by doing so - better understand the match or mismatch between the market strategic positioning of multinational hotel chains and the CEOs' attractiveness perception of the Brazilian market.